Knowledge and action related to stimulation development of stunted children - Krisnana, Ilya; Rachmawali, Praba Diyan; Karimah, Ayu Saadatul; Mhas, Eka Mishbahatul; Benjamin, Lizy Sonia (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the correlation of parental knowledge and parental stimulation with toddler stunting. Method: The cross-sectional study was conducted in April 2020 at the Tlanakan Health Centre, Pamekasan Regency, Indonesia, and comprised mothers of stunted children aged 6-36 months who had no comorbid disease. Data was collected using a questionnaire and a checklist. Data was analysed SPSS with Spearmen Rank correlation. Results: Of the 186 mothers, 125(67.2%) were aged 20-30 years, and 168(90.3%) were housewives. Among the children, 97(52.2%) were boys and 89(47.8%) were girls. The largest age group was that of 25-36 months 80(43%). There was a significant correlation of parental knowledge and stimulation with the development of stunting toddlers (p=0.001). Conclusion: Parental knowledge and actions of developmental stimulation by parents were related to the quality of development of the stunted children. Keywords: Growth disorders, Stunting, Child development, Parental knowledge.